2022
DOI: 10.1136/jnnp-2022-329123
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis disease-modifying therapies and COVID-19 vaccines: a practical review and meta-analysis

Abstract: Studies among people with multiple sclerosis (pwMS) receiving disease-modifying therapies (DMTs) have provided adequate evidence for an appraisal of COVID-19 vaccination policies among them. To synthesise the available evidence addressing the effect of MS DMTs on COVID-19 vaccines’ immunogenicity and effectiveness, following the Cochrane guidelines, we systematically reviewed all observational studies available in MEDLINE, Scopus, Web of Science, MedRxiv and Google Scholar from January 2021 to January 2022 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
47
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 82 publications
8
47
1
Order By: Relevance
“…We demonstrated that PI markedly enhances post‐vaccine humoral and, and, to a lesser extent, cellular responses across DMTs, that is, that the immunologic benefits of PI extended to patients on DMT classes—aCD20 and S1P—that are associated with attenuated post‐infection 44 , 53 , 54 and post‐vaccination responses. 24 , 25 Thus, vaccinated MS patients on aCD20 and S1P therapies who had prior COVID‐19 infection—and these currently comprise the majority of patients in the United States—likely have significantly better immune protection than would be expected based on published studies of vaccination‐only immune responses. 24 , 25 , 55 Moreover, our results suggest that it may be possible to improve humoral and cellular immune response defenses following repeated exposure to virus‐specific antigens even in patients whose immune system has been partially compromised by medications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that PI markedly enhances post‐vaccine humoral and, and, to a lesser extent, cellular responses across DMTs, that is, that the immunologic benefits of PI extended to patients on DMT classes—aCD20 and S1P—that are associated with attenuated post‐infection 44 , 53 , 54 and post‐vaccination responses. 24 , 25 Thus, vaccinated MS patients on aCD20 and S1P therapies who had prior COVID‐19 infection—and these currently comprise the majority of patients in the United States—likely have significantly better immune protection than would be expected based on published studies of vaccination‐only immune responses. 24 , 25 , 55 Moreover, our results suggest that it may be possible to improve humoral and cellular immune response defenses following repeated exposure to virus‐specific antigens even in patients whose immune system has been partially compromised by medications.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 Thus, vaccinated MS patients on aCD20 and S1P therapies who had prior COVID‐19 infection—and these currently comprise the majority of patients in the United States—likely have significantly better immune protection than would be expected based on published studies of vaccination‐only immune responses. 24 , 25 , 55 Moreover, our results suggest that it may be possible to improve humoral and cellular immune response defenses following repeated exposure to virus‐specific antigens even in patients whose immune system has been partially compromised by medications. By its nature, exposure to viral infection is associated with unpredictable, potentially serious short‐ and long‐term adverse events and is inadvisable for anyone, especially the immunocompromised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower effective cellular immune responses through CD4 + and CD8 + T lymphocytes after SARS-CoV-2 vaccination were also suggested for MS patients during interferon, fingolimod and cladribine treatments ( Etemadifar et al., 2022 ; Gombolay et al., 2022 ; Iannetta et al., 2022 ; Tortorella et al., 2022 ).…”
mentioning
confidence: 98%
“…Regarding vaccination, MS patients presented different neutralizing antibody responses against SARS-CoV-2 (77%) vs. healthy controls (93%). MS patients during disease-modifying therapies (DMTs) exhibited: >93% positive antibody responses during glatiramer acetate, beta-interferons, dimethyl-fumarate, teriflunomide, alemtuzumab, and natalizumab; while those treated with fingolimod (27%) and anti-CD20 therapies (44%) showed lower positive antibody responses ( Etemadifar et al., 2022 ; Gombolay et al., 2022 ).…”
mentioning
confidence: 99%